The role of the malay archipelago scholars in terengganu in the development of the Shafi'i sect - Zulkifli, Wan (AENSI, 2012)
The influence of the Shafi'i sect in Terengganu is apparent to others less prominent schools of thought. The influence of this sect cannot be obtained except by recalling the history and background of Islamization in the state. This can be seen from the point of receipt and return-oriented preachers Shafi'i, local scholars and works of local scholars. Hence this paper will delve into the influences of the Shafi'i sect in Terengganu so strong that it can influence the educational practices, legal and production of a fatwa.